Measurement of body composition and athletic performance during NCAA-Division I women's volleyball and softball seasons - Cahill, S.; Jones, M. T. (The Journal of Strength and Conditioning Research, 2010)
The current study was designed to assess the relationship between body composition and performance testing in NCAA-Division I volleyball and softball athletes. Subjects consisted of NCAA-Division I female volleyball (VB, n = 16) and softball (SB, n = 18) athletes. Body composition utilizing air displacement plethysmography (Bod Pod) and performance testing [vertical jump (VJ), hang clean (HC), bench press (BP), front squat (FS), pro agility (PRO: SB only), t-test (TT:VB only), and 300 yd shuttle run (SR)] were measured immediately following completion of a 4 month off-season training program. Data were analyzed by correlating body fat with performance testing results. Pearson product moment correlation coefficients were computed for each group individually, to determine if there was a relationship between body composition and performance variables. VB athletes A significant positive correlation (p <= .05, r = 0.45) was found between SR times and body composition among the VB group. Therefore, the higher the body fat percentage among VB athletes, the slower the SR time. SB athletes A significant negative correlation (p <=. 05, r = -0.45) was found between body composition and VJ with the SB athletes. Additionally, a significant positive correlation (p <= .01, r = 0.79) was found between body composition and PRO run times with SB. A significant positive correlation (p <= 0.01, r = 0.72) was found between body composition and SR times among the SB group. BP, FS and HC were not significantly related to body composition for either VB or SB groups. In conclusion, a significant relationship was found between body composition and certain performance tests for both SB and VB groups. However, the strength of the relationship between variables in the VB group was not as strong as that observed with the SB group. VB is a sport that requires players to execute similar skills while utilizing quick, reactive multi-directional, movements in a relatively small court. VB athletes tend to have similar body types. Ugarkovic (2) concluded body composition is a weak predictor of performance in sports with athletes of relatively homogeneous body types. Significant relationships were found in the SB group between body composition and the PRO, VJ and SR tests. Unlike the sport of VB, the demands of SB (and baseball) differ by position, resulting in more heterogeneous body types (1). For example, outfielders are more likely to require greater speed than pitchers or catchers in order to move to the ball and catch it out of the air. In-fielders require better agility and faster reaction time. The leaner SB players performed better on the running and agility tests. Therefore, body composition data may be utilized by coaches to determine the most appropriate positional roles for their athletes. Future research that addresses the relationship between body composition and injury may provide a broader understanding of the importance of implementing proper nutrition, strength training, and conditioning programs prior to and during competitive athletic seasons.